Knowledge and practices on reduction of mercury added to medical devices in health workers: Conocimientos y prácticas sobre reducción del mercurio añadido a dispositivos médicos en trabajadores de salud - Vda. de Bambaré, María del Socorro Alatrista-Gutiérrez (2018)
Objectives: To evaluate the level of knowledge and practices in health workers of a Public Hospital III-1on policies and strategies for the reduction of mercury added in thermometers and tensiometers. Methods: Two approaches were used. The first used a database with surveys applied to focus groups and interviews to evaluate policies and practices. The second approach, I use the inventory technique through Direct observation of medical material with mercury. Results: 95% of the respondents report that they aree xposed to materials with mercury. Only 10% know to whom the final disposition is delivered when they are cleaned the spills. This same percentage does not know about the existence of the mercury cleaning kit. Also, with Chi square test x2 (p: 0.02) was determined that there is an association between the low level of knowledge in the existence of a mercury cleaning kit and the risk of exposure to it. It was also determined that this risk has an OR 3.2 IC 95% (1.4-3.5) p: 0.01. Through the ANOVA test (95% significance level p: 0.03). And it was determined that there is a statistically significant difference between the averages of the mercury levels in the areas of emergency, hospitalization and observation. The estimated average being numerically greater in the area of medicine, General Surgery, Oncology and Obstetrics. Conclusion: There is a level of ignorance in the reduction of added mercury and the occupational risk in health workers is considered high. DOI 10.25176/RFMH.v18.n4.1729